The next great Paulie Fink - Benjamin, Ali (Little, Brown and Company, 2019)
Led by new student Caitlyn, seventh-graders at a tiny rural school in Vermont create a reality-show inspired competition to determine who will replace the school's legendary class clown, Paulie Fink.